Pengaruh Persepsi pada Atasan, Orientasi Kerja Dan Pengembangan Diri Terhadap Kemampuan Pengelolaan Kelas - Agus Susiyowadi (Jurnal Penelitian dan Pendidikan IPS, 2019)
This study aims 1. To determine the effect of perception on the behavior of superiors , work orientation and self development towards classroom management abilities, 2 To determine the effect of perception on the behavior of superiors on the ability of classroom management, 3. To determine the effect of work orientation on the ability of class management, and 4. To determine the effect of self-development on the ability of classroom management. This research is a quantitative research. The population of this study were all teachers in Diponegoro Dampit Education, which totaled 82 teachers. The sampling technique uses total sampling because all populations are used as respondents. Hypothesis testing results show 1. There is a perception effect on supervisor's behavior, work orientation and self-development on the ability of classroom management because of the analysis s data obtained a calculated F score of 11, 984 and the significance is 0,000 <0.05 which means there is an influence of perception on the behavior of superiors, work orientation and self-development on the ability of classroom teacher management, 2. There is a positive influence of perception on the behavior of superiors on the ability of teacher classroom management because of the analysis of the data obtained t count score of 5.686 and significance of 0.000 <0.05 which means there is an effect of perceptions on the behavior of superiors on the ability of classroom management of teachers, 3. There is an influence of work orientation on the ability of classroom management because of the analysis of the data obtained a t count score of 5.296 and the significance is 0.000 <0.05 which means there is an influence of work orientation on the ability of classroom teacher management, and 4. There is an effect of self-development on the ability of classroom management because From the analysis of the data obtained a t count score of 6.581 and its significance 0.000 <0.05, which means there is an influence of self-development on the ability of teacher classroom management